Eosinophilic Syndromes Associated With Daptomycin Use: Re-exposure Hypersensitivity Pneumonitis and Prior Peripheral Eosinophilia. (16th March 2022) - West, Katelyn A; Sheeti, Ahmed; Tamura MacKay, Kimberly; Forrest, Graeme N
Abstract: Background: Daptomycin pulmonary eosinophilia (DPE) has been well described in case reports and reporting from the Food and Drug Administration. We report 3 eosinophilic syndromes associated with daptomycin use. Methods: This is a retrospective review of all patients who received daptomycin (inpatient or outpatient) from 2010 to 2020 at the Veterans Affairs Portland Healthcare System. Patients who developed DPE while receiving daptomycin were evaluated to determine risk factors. Data collected included daptomycin dose and duration, body mass index, creatinine clearance, and peripheral eosinophilia. Results: Of 330 patients who received daptomycin, 81.5% developed a peripheral eosinophilia, with 109 (33%) developing peripheral eosinophilia ≥5%. Fifty-one (16%) met criteria for DPE. Primary DPE occurred in 38 of the 51 patients with a median 26 days of treatment, and 49% had peripheral eosinophilia ≥5%. Re-exposure DPE occurred in the other 13 patients and occurred a median of 3 days after initiation of daptomycin. The presence of an elevated peripheral eosinophilia of ≥5% during daptomycin usage was significantly associated with primary (odds ratio [OR], 2.23; 95% CI, 1.2–4.09; P = .008) and re-exposure DPE (OR, 12; 95% CI, 1.6–103; P = .003). All patients recovered after withdrawal of daptomycin without complications. Conclusions: There are 3 daptomycin eosinophilic syndromes: peripheral eosinophilia, primary DPE occurring about 4 weeks into therapy, and re-exposure DPE. Elevated peripheral eosinophilia ≥5% was a risk factor for both primary and re-exposure DPE, but still identified about half the cases. Peripheral eosinophilia should be carefully monitored during daptomycin treatment, and clinicians should be aware that prior eosinophilia may predict an acute pulmonary reaction upon daptomycin re-exposure.